(untitled) (Gaceta Técnica, 2026)
Generative design is a design approach that uses algorithms and computational techniques to generate and optimize shapes and patterns. This methodology has the potential to revolutionize the structural design process by emerging as a disruptive tool in structural engineering, driving optimization and innovation in design. The importance of generative design in structural engineering lies in its ability to efficiently and sustainably optimize structures, which can reduce costs and construction time. The objective of this article is to identify the generative design parameters that affect the efficiency of structural design. The procedure includes a search in academic databases and the selection of relevant documents exploring its applications in various structural engineering contexts. The search led to a total of 128 documents between 2020 and 2024; applying inclusion and exclusion criteria based on task automation, generation of more efficient designs, and exploration of multiple design options reduced this to ten cases, of which five were exemplified. Finally, it was found that the parameters time, cost, quality, weight, strength, and energy efficiency are identified as key factors within structural design efficiency